American girl - Brady, Jordan, 1964-; Malone, Jena, 1984-; Renfro, Brad, 1982-2008; Mulkey, Chris; Forbes, Michelle, 1965-; Collins, Clifton, Jr.; Gage, Kevin, 1958-; Mercurio, Micole; Von Detten, Erik.; Hennings, David; Plessner, Amotz; Tomorrow Film Corporation; et al. (Los Angeles, CA : MGM Home Entertainment, 2005)
Rena, is a teenager, who wants to kill herself because she thinks that her life isn't worth anything. Pregnant and idealistic, Rena finds that her chaotic trailer-park existence conflicts with her dreams of having the perfect family.
Originally released as a motion picture in 2002.
Director of photography, David Hennings ; editors, Janice Hampton, Shawna Callahan ; music, Amotz Plessner ; costume designer, Niklas S. Palm ; production designer, Cosmas A. Demetriou.
Jena Malone, Brad Renfro, Chris Mulkey, Michelle Forbes, Clifton Collins, Jr., Kevin Gage, Micole Mercurio, Erik Von Detten.
MPAA rating: R; sexual content, language, teen suicidal behavior and brief drug use.
DVD, region 1, widescreen (1.85:1) presentation; Dolby Digital surround.
English dialogue, English, French or Spanish subtitles; closed-captioned.
Keywords: Teenage pregnancy -- Drama; Teenagers -- Suicidal behavior -- Drama; Fathers and daughters -- Drama; Feature films; Black humor; Video recordings for the hearing impaired; French language materials; Spanish language materials